PENGARUH APLIKASI PUPUK N DAN BIOCHAR TERHADAP KELIMPAHAN POPULASI COLEOPTERA PADA LAHAN KOMODITAS SORGUM - Lende, Aristo Kristian; Wibowo, Dennis; Agastya, I Made Indra; Hamzah, Amir; Pramana, Bintang Arya (Universitas Tribhuwana Tunggadewi, 2025)
Coleoptera play a crucial role in maintaining the balance of agroecosystems through decomposition, nutrient cycling, and biological control. This study aimed to examine the effects of nitrogen (N) fertilizer and rice husk biochar on Coleoptera population abundance in a sorghum (Sorghum bicolor L.) plantation. Conducted at UNITRI Science Technopark, the experiment used a Randomized Complete Block Design with eight treatment combinations of N fertilizer (0, 100, 150, 200 kg/ha) and biochar (5 tons/ha), replicated three times. Coleoptera specimens were collected using pitfall traps and analyzed with ANOVA and DMRT. Results demonstrated that N fertilizer variation had no significant effect (p0.05) on Coleoptera abundance, while biochar application consistently and significantly increased individual counts (p0.05). From 1,533 identified individuals belonging to 11 morphospecies, the distribution was nearly balanced between natural enemies (777 individuals) and other insects. Biochar enhanced soil insect abundance by improving habitat quality, indicating its positive role in supporting Coleoptera populations and its potential as a key component of biodiversity conservation-based sustainable soil management.